PLL-g-HPA Hydrogel Loaded Human Umbilical Cord Mesenchymal Stem Cells Promote Burn Wound Healing in Rat Model by Regulating Inflammation Response - Tian L; Wang Z; Lei T; Feng L; Li Y; Wang K; Zhang Y; Zhang C; Liu J; Xing H; Ren W (Journal of Inflammation Research)
Linqiang Tian,1,2 Zhaodong Wang,1,2 Tingting Lei,1,3 Lili Feng,1 Yanyan Li,1 Kunxi Wang,1 Yue Zhang,1 Chengshu Zhang,4 Jie Liu,1 Hongxia Xing,3 Wenjing Ren5 1Henan Key Medical Laboratory of Traumatics and Orthopaedics’ Research, The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, People’s Republic of China; 2Department of Orthopedics Surgery, The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, People’s Republic of China; 3Department of Neurology, The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, People’s Republic of China; 4Department of Burn and Plastic Surgery, General Hospital of PINGMEI SHENMA Group, Pingdingshan, People’s Republic of China; 5Clinical Medical Center of Tissue Engineering and Regeneration, Xinxiang Medical University, Xinxiang, People’s Republic of ChinaCorrespondence: Hongxia Xing; Wenjing Ren, Email xhxwh02@163.com; xxmu_rwj@163.comPurpose: Treatment of severe burn wound injury remains a significant clinical challenge as serious infections/complex repair process and irregulating inflammation response. Human umbilical cord mesenchymal stem cells (hUC-MSCs) have a multidirectional differentiation potential and could repair multiple injuries under appropriate conditions. Poly(L-lysine)-graft-4-hydroxyphenylacetic acid (PLL-g-HPA) hydrogel is an enzyme-promoted biodegradable in hydrogel with good water absorption, biocompatibility and anti-bacterial properties. Therefore, the aim of this study was to evaluate the therapeutic effect of hUC-MSCs combined with PLL-g-HPA hydrogel on full thickness burn injury in rat model.Methods: The PLL-g-HPA hydrogel was developed and characterized by Scanning Electron Microscopy (SEM), Fourier-Transform Infrared Spectroscopy (FTIR), Hydrogen-1 nuclear magnetic resonance (H-NMR). The cytotoxicity to human foreskin fibroblasts (HFF) were assessed by CCK-8 assay and live/dead quantification and antibacterial activity against Escherichia coli and Staphylococcus aureus was also detected by colony forming unit. A full-thickness burn wound injury model in 12 SD rats was established, and the therapeutic effect of PLL-g-HPA hydrogel combined with hUC-MSCs was detected by healing time/Histology/inflammation factor expression level.Results: The findings from SEM, FTIR, and HFF analyses demonstrated the successful synthesis of PLL-g-HPA hydrogels. These hydrogels exhibited low cytotoxicity at minimal concentrations while maintaining excellent moisture retention and antibacterial properties. Compared to the control group, treatment with PLL-g-HPA hydrogel in conjunction with hUC-MSCs significantly enhanced wound healing, modulated inflammatory responses, and promoted angiogenesis as well as re-epithelialization in rat models.Conclusion: The PLL-g-HPA hydrogel in conjunction with hUC-MSCs represents a promising therapeutic approach for the management of burn wounds.Keywords: rat burn model, wound healing, human umbilical cord mesenchymal stem cells, p-hydroxyphenylacetic acid grafted poly-l-ysine hydrogel